Investigation of ZnO single crystals subjected to a high uniform magnetic field in the IR spectral range - Venger, E.F.; Evtushenko, A.I.; Melnichuk, L.Yu.; Melnichuk, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Based on the experimental data obtained, we performed the theoretical
investigation of the external reflectance coefficients of uniaxial optically anisotropic
polar ZnO single crystals subjected to the action of a high uniform magnetic field that is
parallel to the crystal axis С and the surface under the condition that E⊥B
(the Voigt
configuration, Fig. 1). For the first time, we have found the regions in the external
reflection spectra of ZnO single crystals, where new oscillations appear which are due to
the effect of a high uniform magnetic field. A possibility of solving the direct and inverse
problems in such a case is demonstrated.